Implementasi Business Intelligence untuk Analisa dan Visualisasi Data Penyebab Kematian Di Indonesia Menggunakan Platform Tableau - Lathifah Dini Rachmawati; Firman Noor Hasan (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2023)
Factors causing death in Indonesia are increasing, and many of them cannot identified with certainty. This study aims to identify the most common causes of death in Indonesia. such as causes of death due to social disasters, causes of death due to natural disasters, and causes of death due to non-natural disasters and diseases. This study employs a dataset method from www.kaggle.com with a time span of 2012-2021. The results of this study are reports in the form of a visualization dashboard using Tableau that contains information on the most common causes that occur in Indonesia with a range from 2012 to 2021 so that it can be used as a reference to support decision-making. In conclusion, the number of deaths in 2012–2021 was caused by the highest number of deaths due to natural disasters caused by earthquakes and tsunamis, which accounted for 2,615 deaths. Furthermore, the most cases of death due to non-natural disasters and diseases were caused by COVID-19, namely 144,094 deaths. And the most cases of death due to social disasters were caused by social conflict or social unrest, with 69 deaths.